Expression of PD-L1 (DAKO 28-8) in Urothelial Carcinoma of Urinary Bladder - Azmat, Henna; Masood, Areeba; Sohail Chaudry, Summaya; Mushir, Syeda Iqra; Khalid Sheikh, Ahmareen; Kiran Riaz, Syeda (Asian Pacific Journal of Cancer Biology, 2024)
Background: Around 90% of bladder cancers are urothelial carcinoma. Recent advancements in treatment have shifted towards targeted therapies, particularly immunotherapies targeting PD-L1 (Programmed Cell Death Ligand 1). PD-L1, a ligand for PD-1 receptors, helps cancer cells evade the immune system. Various factors, including genetic alterations, lead to its upregulation in cancer cells. Immunotherapies aim to block this pathway, making cancer cells more susceptible to the immune response. Materials and Methods: This study was conducted at the Department of Pathology, Pakistan Institute of Medical Sciences, Islamabad. Fifty-six cases of urothelial carcinoma were included. Immunohistochemistry was performed using the PD-L1 Dako 28-8 clone on prepared tissue sections. PD-L1 positivity was determined by brown membrane staining in tumor cells, and the expression was scored using the Tumor Proportion Score (TPS). Results: The median patient age was 63 years (±7 years). The highest frequency (58.9%) of PD-L1 expression occurred in the age range of 56 to 65 years. However, there was no significant association between PD-L1 expression and age groups. Out of the 56 cases, 64.3% had a TPS of ≥5%. Among the 76.7% of high-grade cases, 72% had a TPS ≥5%, whereas 28% had a TPS <5%. Among the 23.2% of low-grade cases, 61.5% had a TPS <5%, and 38.5% had a TPS ≥5%. Conclusion: Sixty-four percent of urothelial carcinoma cases showed PD-L1 expression. A significant association (p = 0.02) between PD-L1 expression and high-grade urothelial carcinoma was found using Pearson’s Chi-square test.